2007
DOI: 10.1157/13110311
|View full text |Cite
|
Sign up to set email alerts
|

Oral rush desensitization to cow milk. Following of desensitized patients during three years

Abstract: We report the induction of tolerance in four patients with severe IgE-mediated cow's milk allergy, with an oral rush desensitization by introducing increasing daily doses of cow's milk (CM) for 5 days under clinical conditions in order to enable the patients to tolerate 200 ml of CM daily. Our results indicate that we can induce clinical tolerance in CM allergy by oral administration of progressive doses of milk. After three years of following, the four patients are taking CM with good tolerance. Specific IgE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…In the last decade, a number of studies have reported positive results with oral desensitization to cow's milk. Most of the published series involve patients with severe clinical manifestations and who are over age 5 [11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, a number of studies have reported positive results with oral desensitization to cow's milk. Most of the published series involve patients with severe clinical manifestations and who are over age 5 [11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Although limited, published evidence shows oral desensitization to be a possible intervention [11][12][13][14][15][16][17]. Previous studies have been carried out in children over 5 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…Martorell et al. (15) have written about four children who had anaphylactic reactions to CMP: after 3 yr from the reaction, all these children well tolerated cow milk. Meglio et al.…”
Section: Maintenancementioning
confidence: 99%
“…5 Tal como acontece com outras formas de imunoterapia, podem ocorrer reações adversas locais ou sistémicas, de ligeiras a muito graves, sendo estas possíveis em qualquer fase do tratamento, mas sendo muito mais frequentes na fase inicial da indução. 6 Perante as várias limitações dos protocolos existentes, de entre as quais se destaca a duração prolongada dos protocolos convencionais 12 e o elevado número de reações adversas dos protocolos rush, 13 o Centro de Alergia 6 desenvolveu um protocolo misto, sublingual e oral, utilizando como extrato alergénico LV puro em natureza. As doses iniciais sublinguais (contacto com a mucosa oral durante 2 a 3 minutos, eliminando posteriormente o alergénio), são seguidas da ingestão oral de doses progressivamente crescentes de LV, atingindo a dose alvo de 200 mL/dia, num intervalo médio de 20 semanas, sendo esta uma dose consensualmente aceite como critério de sucesso da intervenção.…”
unclassified